ZUBDAT AL-FIKRA AS A SOURCE ON THE HISTORY OF KAY-KAVUS II AND URBAY-KHATUN - Sabitov Ж.М.; Tuleubayeva С.А. (Journal of Oriental Studies, 2024)
Zubdat al-Fikra is an important source on the history of the Golden Horde, the Ilkhanate, the Rum Sultanate and Mamluk Egypt. The purpose of this study is to analyze the information from the Arabic-language source Zubdat al-Fikr regarding the Seljuk Sultan Izz ad-Din Kay Kavus II (Konya or Rum Sultanate) and his wife Urbay-Khatun (Daughter of Berke, the ruler of the Golden Horde). This article will introduce new information about the life of Izz ad-Din Kay Kavus II and his wife Urbay-Khatun. The materials of the study are extracts from the Arabic-language source Zubdat al-Fikr regarding the Seljuk Sultan Izz ad-Din Kay Kavus II and his wife Urbay-Khatun. Previously, a small excerpt from this work (one paragraph in size) was introduced into scientific circulation by V. Tiesenhausen in 1884. In this article, 4 new excerpts from Zubdat al-Fikr will be introduced into scientific circulation in Russian and information regarding the old translated excerpt will be supplemented. The main research method here will be the methods of external and internal criticism of sources. We have discovered excerpts from Zubdat al-Fikr that are important for the history of the Golden Horde, which allow us to look at certain aspects of the history of the Golden Horde in a new way. We have introduced new information on the history of the Golden Horde and the Konya Sultanate into scientific circulation. New data on the life of Urbay-khatun, the daughter of the ruler of the Golden Horde Berke, have been added. New scientific discoveries concerning the biography of Urbats-Khatun, including her non-hostile relations with the Hulaguids, provide new perspectives for studying the Ilkhan-Jochid relations. Keywords: Zubdat al-Fikra, Tawarikhi Guzidayi Nusrat-name, Ulus of Jochi, Izz ad-din Kay Kavus II, Urbay-Khatun.